Padua Score and Coagulopathy Parameters on Survival of COVID-19 Patients at Prof Dr. R. D. Kandou General Hospital Manado - Rotty, Linda; Hendratta, Cecilia; Damay, Viky; Haroen, Harlinda; Lasut, Pearla; Wariki, Windy (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Coagulopathy in coronavirus disease 2019 (COVID-19) patients causes a prothrombotic state that increases the risk of thromboembolism. The Padua score and coagulopathy parameter including D-dimer values, fibrinogen, prothrombin time (PT), activated partial thromboplastin time (aPTT), and platelet counts are very important parameters to determine risk of thrombosis and mortality in hospitalized COVID-19 patients. AIM: This study aimed to assess the prognosis of COVID-19 patients with Padua score and coagulopathy parameters. METHODS: This retrospective cohort study was conducted in tertiary university hospital, Prof. Dr. R. D. Kandou Hospital Manado, Indonesia from October 2020 to July 2021. Patients admitted with final diagnosis of COVID-19 confirmed with positive reverse transcriptase-polymer chain reaction test were included in the study. The data were refined by excluding the patients under 18 years old and the patients with no blood test results, D-dimer values, fibrinogen values, PT values, aPTT values, and platelet counts. The association of Padua score and coagulopathy parameters with survival of COVID-19 patients was analyzed by multivariate cox regression and Kaplan–Meier analysis. RESULTS: The probability of survival on day 14 in patients with Padua score <4, D-dimer <0.5 mg/dl, PT ≤16 s, aPTT ≤39 s, and platelets >150,000/μL was 100%, 100%, 84.6%, 81.5%, and 81.4%, respectively. COVID-19 survival was influenced by Padua score ≥4 (heart rate [HR] = 4.199; CI 95% 2.221–7.936), D-dimer ≥0.5 mg/L (HR = 4.772; CI 95% 2.244–10.147), PT >16 s (HR = 2.124; CI 95% 1.608–2.805), aPTT >39 s (HR = 1.449; CI 95% 1.080–1.943), and platelet count <150000/μL (HR = 2.056; CI 95% 1.489–2.840). Padua score has the highest probability of mortality compared to the other coagulopathy parameters (p < 0.001; HR = 3.655; CI 95% 1.927–6.932). CONCLUSION: There was an association of Padua score, D-dimer value, PT value, aPTT value, and platelet count on survival of COVID-19 patients. Padua score being the most influential variable on survivals.